2020
DOI: 10.1159/000508433
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Quality of Life Assessments after Cochlear Implantation in Older Adults

Abstract: Cochlear implants (CI) have increasingly been adopted in older adults with severe to profound sensorineural hearing loss as a result of the growing and aging world population. Consequently, researchers have recently shown great interest in the cost-effectiveness of cochlear implantation and its effect on quality of life (QoL) in older CI users. Therefore, a systematic review and critical evaluation of the available literature on QoL in older adult CI users was performed according to the Preferred Reporting Ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 104 publications
2
27
0
2
Order By: Relevance
“…The patient-reported improvements show that implantation is not only effective in improving speech perception but also in alleviating activity limitations and improving QoL across a wider range of listening situations. Notably, the benefits measured with the NCIQ and SSQ in this study for a Finnish CI population are similar in magnitude to those recently reported in a systematic review by Andries et al (2021) . This similarity emerged despite possible variations across countries and languages: for example, differences in the indications for cochlear implantation between different countries and healthcare systems, or differences in perceived benefits across different languages.…”
Section: Discussionsupporting
confidence: 88%
“…The patient-reported improvements show that implantation is not only effective in improving speech perception but also in alleviating activity limitations and improving QoL across a wider range of listening situations. Notably, the benefits measured with the NCIQ and SSQ in this study for a Finnish CI population are similar in magnitude to those recently reported in a systematic review by Andries et al (2021) . This similarity emerged despite possible variations across countries and languages: for example, differences in the indications for cochlear implantation between different countries and healthcare systems, or differences in perceived benefits across different languages.…”
Section: Discussionsupporting
confidence: 88%
“…This has already been observed by others. Although improvement in QoL and speech perception have been described up to and beyond 2 years, the improvement increased the most within the first 6 months of the device use ( Olze et al, 2011 ; Lenarz et al, 2012 ; Völter et al, 2018 ; Andries et al, 2021 ); only a weak association between health-related QoL and speech perception in CI users has been described in previous studies ( Moberly et al, 2017 ; Vasil et al, 2020 ). In a meta-analysis by McRackan et al (2017) covering 13 articles with 715 subjects, correlation between speech perception measures, such as word or sentence recognition in quiet and sentence recognition in noise, and QoL in total or in the different subscores was only low or even neglectable ( McRackan et al, 2017 ).…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, positive outcomes of auditory rehabilitation with regard to the quality of life (QoL), psychosocial comorbidities, and cognitive functions have been reported ( Olze et al, 2011 ; Völter et al, 2018 ; Häußler et al, 2019 ; Andries et al, 2021 ). Providing subjects with hearing loss with an adequate sensory input is supposed to help to reduce the cognitive load caused by hearing loss and to release other cognitive resources.…”
Section: Introductionmentioning
confidence: 99%
“…Currently there are approximately 750,000 CIs registered worldwide. The CI has been reported to improve hearing ability and life quality in most patients, language development in children, and possibly cognitive function in old adults ( Vermeire et al, 2005 ; Claes et al, 2018 ; Andries et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%